Unusual Reactions Mediated by the Corey-Chaykovsky Reagent to Synthesize Cyclopropa-Fused Dibenzocycloheptanoids - Chattopadhyay, Anwita (IISER Mohali, 2022)
Utilizing the unique characteristics of the sulfoxonium ylides to undergo bi-functionalization reactions, our group has developed several unusual and proficient cyclopropanation strategies to access several highly functionalized and synthetically privileged motifs in single step from easy-to-prepare starting compounds. Subsequently, we planned to extend the scope of these methodologies. Hence, we have investigated the reactivity of sulfoxonium ylides with biaryl enone-aldehyde substrates, as this chemistry with sulfoxonium ylides is yet unexplored with biaryl scaffolds. It has been found that reaction of dioxosulfoxonium methylide (DOSM) with designed biaryl substrates deliver a series of cyclopropa-fused dibenzocycloheptanoid scaffolds in excellent yields. Dibenzocycloheptanoids represent the core of several bioactive natural products.
Keywords: Unusual Reactions; Corey-Chaykovsky; Fused Dibenzocycloheptanoids